The Association Between Dietary Antioxidant Micronutrients and Cardiovascular Disease in Adults in the United States: A Cross-Sectional Study - Yin, Ting; Zhu, Xu; Xu, Dong; Lin, Huapeng; Lu, Xinyi; Tang, Yuan; Shi, Mengsha; Yao, Wenming; Zhou, Yanli; Zhang, Haifeng; Li, Xinli (Frontiers in Nutrition, 2022)
Background：Antioxidant micronutrients represent an important therapeutic option for the treatment of oxidative stress-associated cardiovascular diseases (CVDs). However, few studies have evaluated the relationship between the levels of multiple dietary antioxidants and CVDs. Objective: The study therefore aimed to evaluate associations between dietary antioxidants and total and specific CVDs among a nationally representative sample of adults in the US. Design: In total, 39,757 adults (>20 years) were included in this cross-sectional study from the 2005–2018 National Health and Nutrition Examination Survey. We analyzed dietary recall of 11 antioxidant micronutrients in this population. Multivariate logistic and weighted quantile sum (WQS) regression were both applied to examine the relationships between these antioxidants, alone and in combination, with the prevalence of all CVDs and specific CVDs. The linearity of these correlations was also explored using restricted cubic spline (RCS) regression. Results: Multivariate logistic models showed that, compared with the lowest quartile, the levels of 11 antioxidants in the highest quartile were independently associated with decreased total CVD (all P<0.05). The WQS index showed that, when considered together, the 11 micronutrients were negatively correlated with total CVD (P<0.001) and five specific CVDs (all P<0.05), and selenium had the strongest association (weight = 0.219) with total CVD. Moreover, the RCS model demonstrated that iron, zinc and copper were all negatively and nonlinearly correlated with total CVD, while the eight other micronutrients had nonsignificant, linear, negative relationships with total CVD (P for nonlinearity > 0.05). A piecewise binary logistic regression analysis showed that the inflection points in the relationships between CVD and iron, zinc and copper were 7.71, 6.61 and 0.74 mg/day, respectively. Conclusions: Our findings suggested that high levels of combined dietary antioxidant micronutrients are associated with decreased prevalence of CVDs, and that selenium has the greatest contribution to this association.